What’s inside the box?: Mapping agency and conflict within victims’ organizations - Rudling, Adriana (International journal of transitional justice, 2019)
This article provides a better understanding of victims’ individual-level agency and their differences in terms of transitional justice preferences and capabilities by inquiring into intra-organizational conflict. While it is primarily conceptual, it combines secondary literature with case study material from Colombia and Panama, converging on Latin America as a geographical area and the crime of forced disappearance. Tracing the evolution of the 2004/2005 fragmentation of the Colombian Association of Relatives of Detained Disappeared Persons, it argues that victims’ collective action and perceived homogeneity is a performance that builds on much internal negotiation between members. When deliberations have clear winners, they end in adjustments of the mission statement of the group, purges and voluntary member withdrawal, but fragmentations result from situations where the leaders of opposing coalitions are evenly matched and their proposals equally engaging to peers.